SETTLEMENT ABILITY OF PEARL OYSTER (Pinctada maxima) LARVAE AT DIFFERENT POSITIONS AND DEPTHS COLLECTORS - Mat Sardi Hamzah (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
One of the success factor in the cultivation of pearl oysters (Pinctada maxima) within laboratory scale of is the ability of the larvae to settle on the collector. Stocking collectors which are not on time with an irregular position could cause a decline in seed production. The research was conducted from 25 July to 27August 2011 at Laboratory of Marine Bio-industry Technical Implementatation Unit, Research Centre for Oceanography, Indonesian Institute of Sciences, Lombok, West Nusa Tenggara (NTB). The aim of the study was to observe the attachment of larvae at different position and depth. Analysis of variance showed that larvae settlement was influenced by depth instead of position and the interaction between them. Real Honest Different Test showed that in the 20 cm depth was significantly different from 60 cm and 100 cm in number of larvae attached on the collector. The highest survival rate was in 20 cm depth with 68,98% (516 larvae) while in 60 cm was 17,11% (128 larvae) and 100 cm (9,22% (69 larvae), and the others were attached on the wall of the tank 4,68% (35 larvae). Keywords: settlement ability of pearl oyster’s larvae (Pinctada maxima), collector, depth